A novel method for automated assessment of megakaryocyte differentiation and proplatelet formation. (19th May 2018) - Salzmann, M.; Hoesel, B.; Haase, M.; Mussbacher, M.; Schrottmaier, WC.; Kral-Pointner, JB.; Finsterbusch, M.; Mazharian, A.; Assinger, A.; Schmid, JA.
Abstract: Transfusion of platelet concentrates represents an important treatment for various bleeding complications. However, the short half-life and frequent contaminations with bacteria restrict the availability of platelet concentrates and raise a clear demand for platelets generated ex vivo . Therefore, in vitro platelet generation from megakaryocytes represents an important research topic. A vital step for this process represents accurate analysis of thrombopoiesis and proplatelet formation, which is usually conducted manually. We aimed to develop a novel method for automated classification and analysis of proplatelet-forming megakaryocytes in vitro . After fluorescent labelling of surface and nucleus, MKs were automatically categorized and analysed with a novel pipeline of the open source software CellProfiler . Our new workflow is able to detect and quantify four subtypes of megakaryocytes undergoing thrombopoiesis: proplatelet-forming, spreading, pseudopodia-forming and terminally differentiated, anucleated megakaryocytes. Furthermore, we were able to characterize the inhibitory effect of dasatinib on thrombopoiesis in more detail. Our new workflow enabled rapid, unbiased, quantitative and qualitative in-depth analysis of proplatelet formation based on morphological characteristics. Clinicians and basic researchers alike will benefit from this novel technique that allows reliable and unbiased quantification of proplatelet formation. It thereby provides a valuable tool for the development of methods to generate platelets ex vivo and to detect effects of drugs on megakaryocyte differentiation.